New synonyms and lectotypifications in Sida (Malvaceae-Malveae) reveal the first record and extension of the distribution area of Sida maculata to Brazil - Baracho, George Sidney; Agra, Maria De Fátima (Phytotaxa, 2024)
New synonyms and lectotypes in Sida sect. Cordifoliae (Malvaceae, Malveae) are proposed here and reveal the first record and extension of the distribution area of Sida maculata to the Brazilian semi-arid region. The species was first described in the 18th century for the Caribbean islands of Cuba and the Dominican Republic and for a long time was confused with S. cordifolia, from which it is unquestionably distinct in its leaves, inflorescences and flowers. In Brazil, S. maculata is widely distributed from Maranhão to the north of Minas Gerais and was identified for almost a century in herbaria and local floristic treatments as S. galheirensis. Discussions and photographs of types of S. maculata and related taxa are presented, as well as an updated map of the species’ geographical distribution.